Myopia in secondary school students in Mwanza City, Tanzania: the need for a national screening programme. Issue 11 (1st November 2002) - Wedner, S H; Ross, D A; Todd, J; Anemona, A; Balira, R; Foster, A
Abstract : Background/aims: The prevalence of significant refractive errors and other eye diseases was measured in 2511 secondary school students aged 11–27 years in Mwanza City, Tanzania. Risk factors for myopia were explored. Methods: A questionnaire assessed the students' socioeconomic background and exposure to near work followed by visual acuity assessment and a full eye examination. Non-cycloplegic objective and subjective refraction was done on all participants with visual acuity of worse than 6/12 in either eye without an obvious cause. Results: 154 (6.1%) students had significant refractive errors. Myopia was the leading refractive error (5.6%). Amblyopia (0.4%), strabismus (0.2%), and other treatable eye disorders were uncommon. Only 30.3% of students with significant refractive errors wore spectacles before the survey. Age, sex, ethnicity, father's educational status, and a family history of siblings with spectacles were significant independent risk factors for myopia. Conclusion: The prevalence of uncorrected significant refractive errors is high enough to justify a regular school eye screening programme in secondary schools in Tanzania. Risk factors for myopia are similar to those reported in European, North-American, and Asian populations.